Penanganan Keluhan Tamu Terhadap Pelayanan Front Office pada OTA di Hotel AKB - Damayanti, Kadek Venny; Putra, Dewa Gede; Arthini, Ni Nyoman Suci (Program Studi Manajemen Divisi Kamar, 2024)
Complaints are expressions of guest dissatisfaction with the standard of service and facilities of a hotel that are conveyed verbally or in writing. Therefore, it is necessary to handle complaints properly to provide solutions to guest complaints, Later on, it can restore guest confidence and provide satisfaction and loyalty to guests. This study aims to determine how to handle guest complaints about front office services at OTA at HOTEL AKB. The data was obtained using documentation and interview with Front Office Manager to find out information regarding the criteria for handling guest complaints and the responses that should be given referring to guest complaints in Front Office services.The analysis technique used in this research is descriptive qualitative by first describing the existing problems then describing the suitability of the response to handling guest complaints by the hotel so that conclusions can be drawn. The results of this study indicates that the handling of guest complaints on OTA at HOTEL AKB still does not meet applicable standards. This can be proven by the conclusions obtained, namely from seven guest complaints regarding front office services, only three complaints have received a response from the hotel, but two points in the standard handling of guest complaints have not been done. Meanwhile, four other guest complaints have not received a response from the hotel, this means that six important points in the standard for handling guest complaints have not been carried out due to high workload during high or peak occupancy and this also happens because the time to respond to guest complaints is longer than expected. Handling guest complaints at OTA is not implemented due to a lack of regular training